Prediction of Hernia Formation or Cracking of Boiler Water Tubes due to Corrosion - Traore, Sibiri (European Scientific Journal, ESJ, 2024)
This work is part of the preventive maintenance of equipment and installations of a steam thermal power plant. At the level of the boiler water tubes, hernia formation, cracking, and perforation are recurrent and appear when the thermal power plant is operating at full speed. This damage is largely due to corrosion and thinning of the pipe wall. When corrosion progresses, the thinning of the tubes progresses simultaneously. From a certain value of the wall thickness, under the effect of water/steam pressure, the tubes deform and burst. In such a situation, it is important to predict the approximate time of occurrence of such damage, in order to undertake the appropriate maintenance deaths. For this, we seek to determine the corrosion rate and stresses in the tubes due to water/steam pressure, in order to find the maximum limit time not to exceed to replace the tubes. Tubes must absolutely be replaced before the end of this time limit to prevent the aforementioned damage.